Electrochemical Reduction and Oxidation of Copper, Lead Complex and Metal-Free Phthalocyanine - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
In this study, polarographic reduction of crown-ether substituted metal-free (H(2)Pc), copper(II) (CuPc) and lead(II) (PbPc) phthalocyanine complexes were examined in aqueous medium on a dropping mercury electrode. All measurements were carried out at 25 1 C. A saturated calomel electrode was employed as the reference electrode. Sodium nitrate. potassium nitrate and tetrabutylammonium chloride were used as the supporting electrolytes. Solutions were buffered with CH(3)COONa center dot 3H(2)O, K(2)HPO(4) and H(3)B0(3 center dot) Polarograms were recorded at different pH values. In order to find out whether the electrochemical reactions are diffusion controlled or not, polarograms were also recorded as a function of the mercury column's height. While two reduction waves were observed with H2Pc, CuPc gave three reduction waves at all pH values within the range of 2-12. PbPc showed one, two or three reduction waves depending on the pH values. From the logarithmic analysis of the current-voltage curves the kinetic parameters (alpha n and k(f.h)(0)) were calculated. The results showed that reduction processes of all complexes on dropping mercury electrode in aqueous medium were diffusion controlled and irreversible. Generally, the reduction half-wave potentials of the complexes were found to shift to more negative values with increasing pH. It was also found that the heterogeneous standard reduction rate constants (k(f.h)(0)).of the complexes decrease with increasing pH. These findings were attributed to the involvement of protons in electrochemical reactions. Since it is not possible to determine the oxidation of complexes by polarography, voltamograms by cyclic voltammetry at various solvents at the positive potential side against saturated calomel electrode were recorded, but no oxidation peak could be observed.
Keywords: Phthalocyanine; Lead; Copper; Electrochemical; IN-SITU SPECTROELECTROCHEMISTRY; ACID SODIUM-SALT; CYCLIC VOLTAMMETRY; WATER; DIMETHYLSULFOXIDE